New therapeutic agents in diabetic nephropathy - Kim, Yaeni (Korean J Intern Med, 2017)
Studies investigating diabetic nephropathy (DN) have mostly focused on interpreting the pathologic molecular mechanisms of DN, which may provide valuable tools for early diagnosis and prevention of disease onset and progression. Currently, there are few therapeutic drugs for DN, which mainly consist of antihypertensive and antiproteinuric measures that arise from strict renin-angiotensin-aldosterone system inactivation. However, these traditional therapies are suboptimal and there is a clear, unmet need for treatments that offer effective schemes beyond glucose control. The complexity and heterogeneity of the DN entity, along with ambiguous renal endpoints that may deter accurate appraisal of new drug potency, contribute to a worsening of the situation. To address these issues, current research into original therapies to treat DN is focusing on the intrinsic renal pathways that intervene with intracellular signaling of anti-inflammatory, antifibrotic, and metabolic pathways. Mounting evidence in support of the favorable metabolic effects of these novel agents with respect to the renal aspects of DN supports the likelihood of systemic beneficial effects as well. Thus, when translated into clinical use, these novel agents would also address the comorbid factors associated with diabetes, such as obesity and risk of cardiovascular disease. This review will provide a discussion of the promising and effective therapeutic agents for the management of DN.